2013
DOI: 10.3892/ijmm.2013.1311
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-9 regulates the expression of peroxisome proliferator-activated receptor δ in human monocytes during the inflammatory response

Abstract: PPARδ is involved in the inflammatory response and its expression is induced by cytokines, however, limited knowledge has been produced regarding its regulation. Since recent findings have shown that microRNAs, which are small non-coding RNAs that regulate gene expression, are involved in the immune response, we set out to investigate whether PPARδ can be regulated by microRNAs expressed in monocytes. Bioinformatic analysis identified a putative miR-9 target site within the 3′-UTR of PPARδ that was subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 40 publications
3
51
0
2
Order By: Relevance
“…Liao Pan et al, 2009b;To et al, 2009;Wang et al, 2010;Li et al, 2011;Padmanabhan et al, 2012;Jiao et al, 2013;Ma et al, 2013 Kida et al, 2011;Tong et al, 2011;Zhou et al, 2011 NR1C3 Nuclear Receptor miR-130, -27b, -27a Jennewein et al, 2010 Kim et al, 2010;Lee et al, 2012 NR1C2 Nuclear Receptor miR-15a, -199a, -214, -9 Yin et al, 2010el Azzouzi et al, 2013;Thulin et al, 2013 NR1H3 …”
Section: Micrornas Regulate the Expression Of Adme Phase I And Ii Enzmentioning
confidence: 99%
See 1 more Smart Citation
“…Liao Pan et al, 2009b;To et al, 2009;Wang et al, 2010;Li et al, 2011;Padmanabhan et al, 2012;Jiao et al, 2013;Ma et al, 2013 Kida et al, 2011;Tong et al, 2011;Zhou et al, 2011 NR1C3 Nuclear Receptor miR-130, -27b, -27a Jennewein et al, 2010 Kim et al, 2010;Lee et al, 2012 NR1C2 Nuclear Receptor miR-15a, -199a, -214, -9 Yin et al, 2010el Azzouzi et al, 2013;Thulin et al, 2013 NR1H3 …”
Section: Micrornas Regulate the Expression Of Adme Phase I And Ii Enzmentioning
confidence: 99%
“…CYP3A4 can be induced by ligands that bind and activate the pregnane X (PX) receptor (Lehmann et al, 1998). Experimental data also indicate that the level of CYP3A4 is affected by epigenetic factors, including histone acetylation and methylation (Dannenberg and Edenberg, 2006;Kacevska et al, 2012) and also miRNAs.A recent study based upon several different miRNA target prediction programmes identified 105 miRNAs that may potentially interact with CYP3A4 mRNA -124, -203, -26a, -135b, -145 Furuta et al, 2010;Borel et al, 2012 ABCG1 Transporter miR-33 Marquart et al, 2010Rayner et al, 2010 ABCG2/BCRP Transporter miR-520h, -519c, -328, -487a, -181aLiao Pan et al, 2009b;To et al, 2009;Wang et al, 2010;Li et al, 2011;Padmanabhan et al, 2012;Jiao et al, 2013;Ma et al, 2013 Kida et al, 2011;Tong et al, 2011;Zhou et al, 2011 NR1C3 Nuclear Receptor miR-130, -27b, -27a Jennewein et al, 2010 Kim et al, 2010;Lee et al, 2012 NR1C2 Nuclear Receptor miR-15a, -199a, -214, -9 Yin et al, 2010el Azzouzi et al, 2013;Thulin et al, 2013 NR1H3 …”
mentioning
confidence: 99%
“…MiR-9 has been shown to regulate the expression and activation of peroxisome proliferator-activated receptor δ (PPARδ), a cytokine-inducible nuclear receptor involved in the inflammatory response. Lipopolysaccharide-stimulated monocytes show increased expression of miR-9 with a down-regulation of PPARδ [58]. MiR-9 has also been demonstrated to reduce the formation of foam cells, which are derived from macrophages and constitute the fatty streaks of intimal atherosclerotic plaques.…”
Section: Immune Cellsmentioning
confidence: 99%
“…miR9 também é induzido por Helicobacter pilori e Lipopolissacarídeos de parede de Escherichia coli (LPS) de uma maneira Myd88 dependente (Bazzoni et al, 2009;Lario et al, 2012). Esse miRNA demonstrou ter ação reguladora sobre o processo inflamatório em macrófagos ao inibir o recepetor nuclear Peroxissome proliferator-activated receptor δ (PPARδ) em macrófagos (Thulin et al, 2013). Foi demonstrado também que miR9 é capaz de controlar diretamente os efeitos de NFκB, regulando o processo inflamatório em monócitos (Bazzoni et al, 2009).…”
Section: Por Exemplo Mir9 é Induzido Pelos Vírus Hpv Hiv E O Vírus unclassified
“…Foi utilizado para esse primeiro mapeamento o software NextGenMap (Sedlazeck et al, 2013), mas será utilizado também o software TopHat2 (Kim et al, 2013 desempenham uma atividade reguladora sobre a inflamação Gong et al, 2011;Thulin et al, 2013;Zhuang et al, 2012). miR146a inibe a produção de citocinas pró-inflamatórias em células dendríticas ao atuar sobre os mRNAs de elementos da via de TLR TRAF6 e IRAK1 (Park et al, 2014;Saba et al, 2012).…”
Section: Caracterização Das Bases Moleculares Da Suscetibilidade a Cunclassified